Preparation of Al2TiO5-Al2O3 and Al2TiO5-Al2O3-TiO2 Ceramics by High-Energy Ball Milling and Sintering - Reis de Oliveira Caltabiano, Pietro Carelli [UNESP]; de Souza, Marisa Aparecida [UNESP]; Costa Marques, Rodrigo Fernando; Nogueira Campos, Maria Gabriela; de Oliveira Hein, Luis Rogerio [UNESP]; Ramos, Alfeu Saraiva [UNESP] (Trans Tech Publications Ltd, 2012)
The present work reports on the preparation of Al2O3-TiO2 ceramics by high-energy ball milling and sintering, varying the molar fraction in 1:1 and 3:1. The powder mixtures were processed in a planetary Fritsch P-5 ball mill using silicon nitride balls (10 mm diameter) and vials (225 mL), rotary speed of 250 rpm and a ball-to-powder weight ratio of 5:1. Samples were collected into the vial after different milling times. The milled powders were uniaxially compacted and sintered at 1300 and 1500 degrees C for 4h. The milled and sintered materials were characterized by X-ray diffraction and electron scanning microscopy (SEM). Results indicated that the intensity of Al2O3 and TiO2 peaks were reduced for longer milling times, suggesting that nanosized particles can be achieved. The densification of Al2O3-TiO2 ceramics was higher than 98% over the relative density in samples sintered at 1500 degrees C for 4h, which presented the formation of Al2TiO5.
Keywords: Al2O3-TiO2; high-energy ball milling; sintering; biomaterials